Prevention and control practices against Sars-Cov2 infection in the peruvian population - Fernandez-Guzman, Daniel (2021)
Objetive: To describe the prevention and control practices for the infection to SARS-COV2 in the Peruvian population. Material and Methods: Observational descriptive study. We evaluated a non-probabilistic sample of adult residents in some departments of Peru. Preventive practices were evaluated in people without a history of COVID-19 and control practices in people who had suffered it. Results: We evaluated 3630 Peruvians (mean age 25.4 ± 9.5), of that 3231 don't have a history of COVID-19 and 399 who had suffered it. The prevention and control practices that were realized often or always, with more frequencies, was the use of a mask when they go out home (97.9% vs 87.7), cover their nose or mouth when they sneeze (95.4% vs 89.9%), save the distance to other people in the street (91.4% vs 74.7%), wash their hands when they came home (92.5% vs 88.7%), and disinfect the objects and personal places (82.6% vs 77.4%). The 22.1% and 83.7%, the 59.7% and 80.2, and the 8.0% and 16.8% consumed some type of medicine, medicinal plant, and chlorine dioxide to prevent and control the infection, respectively. Conclusion: In general, less than 50% of the participants performed prevention and control practices against COVID-19 often or always.